2018
DOI: 10.1108/bpmj-03-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing supply chain performance through collaborative planning, forecasting, and replenishment

Abstract: Purpose Despite the importance of collaborative planning, forecasting, and replenishment (CPFR), its influence on supply chain innovation capability (SCIC) and supply chain performance (SCP) has not been sufficiently examined. The purpose of this paper is to examine the antecedence of SCP through CPFR and SCIC. Design/methodology/approach Through cluster and stratified random sampling, 286 responses from top managers of 1,574 Nigerian manufacturing companies were analyzed. Data analysis was performed using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 99 publications
(109 reference statements)
1
20
0
2
Order By: Relevance
“…From Table 5, it is revealed that Collaborative Planning, Forecasting and Replenishment (CPFR) (C 5-1 ) and Co-creation (C 5-3 ) have attained weights (.0.1215) and (0.0662) respectively indicating that both these factors are significant in managing buyer and supplier relationships and also enhancing the survivability of SSCs. CPFR (C 5-1 ) is a business activity that unites the intelligence of several SCs and jointly practising forecasting and planning for improving demand visibility and efficiency (Singhry and Rahman 2019). The demand and supply of essentials is outside the boundaries for which the SCs are designed for and thus CPFR will provide the accuracy in forecasting or anticipating demand.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…From Table 5, it is revealed that Collaborative Planning, Forecasting and Replenishment (CPFR) (C 5-1 ) and Co-creation (C 5-3 ) have attained weights (.0.1215) and (0.0662) respectively indicating that both these factors are significant in managing buyer and supplier relationships and also enhancing the survivability of SSCs. CPFR (C 5-1 ) is a business activity that unites the intelligence of several SCs and jointly practising forecasting and planning for improving demand visibility and efficiency (Singhry and Rahman 2019). The demand and supply of essentials is outside the boundaries for which the SCs are designed for and thus CPFR will provide the accuracy in forecasting or anticipating demand.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…As the COVID-19 spreads to new places, the global and local supply chains must implement mitigation and alternative plans. The companies see sustainability as a competitive opportunity for associating with suppliers (Singhry and Rahman 2019 ). Supply chain co-creation in supply chains aims to enhance the process and product while making improvements.…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al (2018) studied the SC integration and operational performance of the original equipment manufacturer in China automotive industries. Singhry and AbdRahman (2019) observed that SC innovation capability effect SC performance. observed that internal structure of organizations also affect financial performance.…”
Section: Performance Measurementmentioning
confidence: 99%